Coping and its importance for quality of life in patients with multiple sclerosis. (April 2014) - Mikula, Pavol; Nagyova, Iveta; Krokavcova, Martina; Vitkova, Marianna; Rosenberger, Jaroslav; Szilasiova, Jarmila; Gdovinova, Zuzana; Groothoff, Johan W.; van Dijk, Jitse P.
Abstract Purpose: The aim of this study was to analyse whether problem-focused coping, coping focused on getting support and coping focused on stopping unpleasant emotions and thoughts are associated with different levels of physical and mental quality of life (PCS, MCS), controlling for gender, age and disease severity among MS patients. Method: The sample consisted of 113 consecutive MS patients (response rate: 79.6%; 77.0% women; mean age 40.8 ± 9.2). Patients completed the Short-Form Health Survey (SF-36) and the Coping Self-Efficacy Scale (CSE). Disability was assessed by Expanded Disability Status Scale (EDSS). The associations between CSE and PCS and MCS were analysed using linear regression. Results: EDSS and age were significantly associated only with PCS. The regression model for problem-focused coping, coping focused on getting support and coping focused on stopping unpleasant emotions and thoughts explained 29%, 24% and 35% of the variance in MCS, respectively. In PCS coping was not significant. Conclusions: Coping is significantly associated with MCS, but not with PCS. Stopping unpleasant emotions and thoughts seems to be the most important type of coping in MS patients. Thus, patients, their caregivers and their physicians should be educated about this type of coping and its positive association with MCS. Implications for Rehabilitation All types of coping are associated positively with mental component of Quality of life. Coping focused on stopping negative emotions and thoughts seems to be very adaptive for patients with MS. This type of coping can help patients with chronic conditions when problem-focused coping can not effectively solve the problem.